Peran Perguruan Tinggi Dalam Pengendalian Faktor Risiko Stroke Melalui Skrining Dengan Pengukur Risiko Jatuh - Lilik Sigit Wibisono; Purna Luberto; Fitratun Najizah; Syurrahmi Syurrahmi; Ni Kadek Krisna Dwi Patrisia; Mutiara Andriyani; Rafif Aydin Maheswara; Aisya Rahmah; Cintya Putri Anisah; Bernadiktus Reynaldo Nathanael; Radhita Ananta Putri (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Stroke is a disease that is the third leading cause of death in the world after heart disease and cancer. Stroke is also the world's leading cause of serious and permanent disability. In the world stroke attacks occur in more than 15 million people each year. Of these 15 million people, 5 million die, and others survive, but experience permanent disability and live dependent on family and society, and a small percentage of people recover as before the stroke (WHO, 2010) to prevent the risk of excessive falls, physiotherapy has a way to prevent it through the Fukuda TEST. This study used a mix-method research design. The participants in this study were parties related to the problem of fall risk prevention, including the community around Tugurejo Semarang Hospital, local government, health cadres and community leaders. Qualitative data collection techniques used structured interview guides and observation and quantitative data in the form of Fukuda Test measurements on the community and IFI members who were present. After the data was obtained, FGD (Focus Group Discussion) was conducted with local government, health cadres and community leaders with the aim of validating the data that had been obtained. A total of 62 patients with unilateral BPPV were included in our study (35 female/27 male). The mean age was 45.3 years (range 23-67 years). Of these patients 51 (83.6%) were posterior and 11 (16.4%) were lateral canal BPPV. Two groups were created due to the FST results. Group 1 consisted of 33 (53.2%) patients with positive FST results and Group 2 consisted of 29 (46.8%) patients with negative FST results. No statistically significant differences were found between the gender and age distributions in Group 1 and Group 2, p=0.7943 and p=0.5262, respectively (Table 1). In addition, the ratio of FST positive and FST negative BPPV patients was not statistically significant. will cause daily activities to be disrupted then Qualitative data processing was carried out using the advocacy method according to the Covey and Miller advocacy framework, so as to obtain complete information related to the root causes of problems to the preparation of fall risk prevention strategies. Based on the results of data processing according to the Covey and Miller advocacy framework, the data is then analyzed through three stages: data reduction, data presentation and conclusion drawing. This research will be conducted at RSUD Tugu, Semarang City, conducted by physiotherapy in collaboration with STIKES KESDAM IV Diponegoro students.